1992
DOI: 10.1128/iai.60.4.1385-1389.1992
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS) from Brucella abortus is less toxic than that from Escherichia coli, suggesting the possible use of B. abortus or LPS from B. abortus as a carrier in vaccines

Abstract: BruceUa abortus may be useful as a component of vaccines. This is because it possesses several unique properties as a carrier that enable it to stimulate human B cells even in the relative absence of T cells. Human immunodeficiency virus type 1 proteins conjugated to B. abortus could induce neutralizing antibodies against human immunodeficiency virus type 1. Recently we showed that the characteristics of lipopolysaccharide (LPS) derived from B. abortus are similar to those of the whole bacterium in that the LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 19 publications
3
33
1
1
Order By: Relevance
“…B. abortus LPS is reported to be a good candidate for a vaccine carrier because of the lower toxicity (13,14). The present study demonstrates that B. melitensis LPS exhibits a strong adjuvant action and that its toxicity was much less than that of E. coli LPS.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…B. abortus LPS is reported to be a good candidate for a vaccine carrier because of the lower toxicity (13,14). The present study demonstrates that B. melitensis LPS exhibits a strong adjuvant action and that its toxicity was much less than that of E. coli LPS.…”
Section: Discussionsupporting
confidence: 50%
“…Further, the O antigen of Brucella LPS is a homopolymer of perosamine (4,6dideoxy-4-formamido-d-mannopyranosyl) (3,27,37). The biological activities such as cytokine production and lethality of S-LPS and rough types of LPS (R-LPS) from various Brucella strains are reported to be lower than those of enterobacterial LPS (4,14,25,29). The lower endotoxicity seems to be responsible for the unique lipid A structure of Brucella LPS.…”
mentioning
confidence: 99%
“…In order to enhance the feasibility of using B. abortus as a potential carrier in vaccines, we extracted the LPS from B. abortus (LPS-BA) and conjugated it to the trinitrophenyl hapten (TNP-LPS-BA). The potential use of LPS from B. abornus in future vaccines is supported by recent toxicology studies performed in our laboratory (10). These studies demonstrated that LPS-BA is 300 to 10,000 times less potent than LPS-EC in a variety of assays, including the rabbit pyrogen test, mortality of D-galactosamine-sensitized mice, and IL-13 and tumor necrosis factor alpha induction from human monocytes.…”
mentioning
confidence: 76%
“…The isotype switching in nude mice is probably attributable to low numbers of T cells found in the peripheral lymphoid organs of these mice (14). The differences in antibody induction between LPS-EC, LPS-BA, and B. abortus may be related to their relative abilities to stimulate IL-1 release from monocytes/macrophages (10), which could af- Ficoll or with 109 organisms of TNP-BA per mouse at 2-week intervals. Sera were collected 5 days after each injection.…”
Section: Figmentioning
confidence: 99%
“…Although B. abortus possesses LPS, the generic endotoxin of Gram-negative organisms, it may derive its inflammatory capacity from lipoproteins. Differently from the LPS from the Enterobacteriaceae, Brucella LPS has thus far been found to be virtually devoid of proinflammatory activity [36]. Moreover, we have shown recently that the production of proinflammatory cytokines by different cell types of the innate immunity is induced by Brucella lipoproteins rather than LPS [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 97%